A multi-threaded time domain TLM algorithm for symmetric multi-processing computers - So, Poman P M; Hoefer, Wolfgang J R (IEEE MTT-S International Microwave Symposium digest, 2001)
A multi-threaded TLM algorithm will be presented in this paper. The algorithm enables time domain field simulators to exploit the full computing power of multi-processor computers, resulting in improved performance of field solver based CAD tools running on multi-processor computers.